Adsortion of lead onto Xanthated modified Rubber (Hevea Brasiliensis) powder - Wan Mohd Khalir, Wan Khaima Azira; Megat Hanafiah, Megat Ahmad Kamal; Mat So'ad, Siti Zaiton; Wan Ngah, Wan Saime; Abdul Majid, Zafri Azran (Asian Network for Scientific Information, 2011)
Rubber (Hevea brasiliensis) leaf powder was modified by xanthation process and its potential in removing toxic Pb(II) ion from aqueous solutions was investigated in batch experiments. Pb(II) adsorption efficiency was found to be affected by several physicochemical parameters such as adsorbent dosage, shaking rate and temperature. The optimum adsorbent dosage was found to be at 0.02 g with more than 80 % Pb(II) removal. The amount of Pb(II) adsorbed (mg/g) increased with increasing agitation rate but decreased with increasing adsorbent dosage and temperature. Thermodynamic parameters such as enthalpy change (ΔHº), free energy change (ΔGº) and entropy change (ΔSº) were computed and Pb(II) adsorption process was found to be exothermic. Fixed-bed column fitted well the Thomas and Yoon-Nelson models with correlation coefficients of R2 > 0.95.